Colloidal stability of water-based carbon nanotube suspensions in electrophoretic deposition process: Effect of applied voltage and deposition time - Ervina, J.,; Ghaleb, Z.A.,; Hamdan, S.,; Mariatti, M. (Elsevier Ltd, 2019)
The addition of nanoparticles as reinforcement to conventional fiber reinforced plastics shows great promise to be used as advanced structural materials. The aim of this study is to produce a hierarchical carbon fiber (CF)-multi-walled carbon nanotubes (MWCNTs) using electrophoretic deposition (EPD) method. Realizing the benefits of the water-based EPD method, the effect of voltages and deposition times on the MWCNTs stability in distilled water (DW) were investigated. The UV–Vis and stability test observations demonstrated better dispersion and higher colloidal stability of MWCNTs in DW suspension within a short time. With the presence of an applied voltage, MWCNTs-DW suspension was well dispersed with minimal sedimentation. Flexural properties of laminate composites and Field Emission Scanning Electron Microscopy (FESEM) images revealed the best EPD condition for the deposition of the MWCNTs onto the CF was determined to be a deposition time of 5 min and applied voltage of 20 V. © 2018 Elsevier Ltd